From market concentration to political corruption - Glenna, Leland (Journal of Agriculture, Food Systems, and Community Development, 2024)
First paragraph: The government and the press in the United States tend to define corruption narrowly as the misbehavior of individual politicians. They turn a blind eye to systematic corruption such as, for example, the wealthiest people and corporations using campaign contributions to buy political influence. A politician who takes a cash bribe in exchange for a political favor might be deemed corrupt. In contrast, a politician who derails a piece of legislation after receiving a large campaign contribution is operating within the limits of the U.S. campaign laws and is, therefore, not deemed corrupt. . . .